Impact of problem-based charting on the utilization and accuracy of the electronic problem list. (18th January 2018) - Li, Ron C; Garg, Trit; Cun, Tony; Shieh, Lisa; Krishnan, Gomathi; Fang, Daniel; Chen, Jonathan H
Abstract: Objective: Problem-based charting (PBC) is a method for clinician documentation in commercially available electronic medical record systems that integrates note writing and problem list management. We report the effect of PBC on problem list utilization and accuracy at an academic intensive care unit (ICU). Materials and Methods: An interrupted time series design was used to assess the effect of PBC on problem list utilization, which is defined as the number of new problems added to the problem list by clinicians per patient encounter, and of problem list accuracy, which was determined by calculating the recall and precision of the problem list in capturing 5 common ICU diagnoses. Results: In total, 3650 and 4344 patient records were identified before and after PBC implementation at Stanford Hospital. An increase of 2.18 problems (>50% increase) in the mean number of new problems added to the problem list per patient encounter can be attributed to the initiation of PBC. There was a significant increase in recall attributed to the initiation of PBC for sepsis (β = 0.45, P < .001) and acute renal failure (β = 0.2, P = .007), but not for acute respiratory failure, pneumonia, or venous thromboembolism. Discussion: The problem list is an underutilized component of the electronic medical record that can be a source of clinician-structured data representing the patient's clinical condition in real time. PBC is a readily available tool that can integrate problem list management into physician workflow. Conclusion: PBC improved problem list utilization and accuracy at an academic ICU.